Hot injection synthesis of CuInS2 nanocrystals using metal xanthates and their application in hybrid solar cells. (30th November 2018) - Perner, Verena; Rath, Thomas; Pirolt, Franz; Glatter, Otto; Wewerka, Karin; Letofsky-Papst, Ilse; Zach, Peter; Hobisch, Mathias; Kunert, Birgit; Trimmel, Gregor
Abstract : Copper indium sulfide nanocrystals with sizes of 3–4 nm were synthesized from metal xanthates in a hot injection reaction. After ligand exchange, their performance as acceptors in polymer/nanocrystal hybrid solar cells was evaluated. Abstract : Copper indium sulfide (CuInS2 ) nanocrystals with a size of 3–4 nm and a chalcopyrite crystal structure were synthesized from copper and indium xanthates as precursors in a hot injection synthesis performed at a temperature of 200 °C. Dioleamide molecules served as stabilizing ligands and were exchanged to 1-hexanethiol after the synthesis. TEM images reveal that after the ligand exchange process, the inter-particle distance is significantly reduced and the nanocrystals agglomerate slightly, which is also indicated by small angle X-ray scattering and AFM measurements. Information about charge transfer between the conjugated polymer PCDTBT and the nanocrystals was gained from photoluminescence quenching measurements. Furthermore, the prepared CuInS2 nanoparticles with an optical band gap of 1.57 eV were applied as acceptors in polymer/nanocrystal bulk heterojunction solar cells and their performance was evaluated. The obtained solar cells showed high open circuit voltages up to 730 mV and overall power conversion efficiencies of 0.23%.